MATHEMATICAL MODELING OF THE BREAKTHROUGH CAM PROFILE OF THE ENGINE GAS DISTRIBUTION MECHANISM - Mirzaabdullaev J.B.; Rakhmatova F.M.; Yangibayev A.I. (International Journal of Innovations in Engineering Research and Technology, 2021)
The equation of movement of a flap with allowance for of elastic deformations of a valve actuator permitting is maneuvered to calculate a profile of a shock-free cam supplying a desired law of movement of a flap. It ensures maximal filling up of the barrel and conservation of the marked phases of a valve timing, does not enable oscillating a flap, the breakoff it from a saddle on landing and does not enable a undue wear of parts of a valve operating mechanism.